Antidiabetic Activity of Asam Paya (Eleiodoxa conferta) Fruit Vinegar through α-Amylase Inhibition: A Spectrophotometric Study - Jessica Imeliana; Emilda Sari; Ratih Indrawati (Public Health Frontier, 2026)
Background: Diabetes mellitus remains a growing global health burden, affecting an estimated 537 million adults in 2021 and projected to reach 783 million by 2045. Controlling postprandial hyperglycemia through inhibition of the α-amylase enzyme is one accessible non-pharmacological strategy. Asam paya (Eleiodoxa conferta), a swamp palm fruit native to West Kalimantan, Indonesia, is traditionally processed into fruit vinegar and contains acetic acid and secondary metabolites with potential enzyme-inhibitory activity. This study determined the antidiabetic activity of asam paya fruit vinegar as an α-amylase inhibitor using a spectrophotometric method. Methods: A quasi-experimental design with purposive sampling was used. Vinegar was produced by sequential alcoholic and acetic fermentation (11 days) of asam paya fruit juice, then evaluated at five concentrations (1000–5000 ppm) with five replicates each (n = 25). Vinegar quality (sugar, acetic acid, pH) and phytochemical content (flavonoid, tannin, alkaloid, saponin) were assessed. α-Amylase inhibition was measured by the starch–iodine (Fuwa) method at λmax 580 nm using UV-Vis spectrophotometry, with acarbose as positive control; IC50 was determined by linear regression. Results: The vinegar contained 5% sugar, 4.56% acetic acid, and pH 5.20, meeting SNI 01-3711-1995 vinegar quality standards. Phytochemical screening detected tannin and saponin but not flavonoid or alkaloid. The regression equation for vinegar was y = 0.0014x + 20.833 (R² = 0.9852), giving IC50 = 20,833.6 ppm, while acarbose showed y = 0.0094x + 49.707 (R² = 0.9824), IC50 = 32 ppm. Conclusion: Asam paya fruit vinegar met national vinegar quality standards but showed only very weak α-amylase inhibitory activity (IC50 > 200 ppm) relative to acarbose, most plausibly reflecting its low acetic acid content and the limited secondary metabolite profile retained after acetic fermentation.